Kondisi Poshuman di Mongrel (2021) Karya Sabda Armandio - Helmi Naufal Zul'azmi (Sanata Dharma University, 2023)
This article aims to examine the relations of posthuman subjects formed through language in Mongrel’s fiction. Relations of posthuman subjects will always be surrounded by the current situation being faced, so it is no longer necessary to differentiate human and nonhuman hierarchically. Mongrel is a fictional story published serially in the mass media KumparanPlus in 2021. This article uses a discursive approach to gain knowledge about the relationship of posthuman subjects by connecting meaning, representation, and context. This article shows that the posthuman conditions that surround characters in Mongrel include the economic crisis, advanced capitalism, and the creation of paguyuban (community), technology and artificial intelligence, and the work of shamans and the existence of Dimensi Kalia. In some ways, the posthuman condition in Mongrel exhibits the attempt to surpass the dichotomies especially between human/animal/plant/technology. The posthuman condition in Mongrel leads to a double-edged sword, namely the paguyuban going hand in hand with advanced capitalism. Mr. Polo, as the metaphor of advanced capitalism, no longer utilizes the dichotomy of human/nonhuman and modern science/shaman to develop his business. This is also the case for the paguyuban. However, what sets Mr. Polo apart is his attempt to control nonhuman entities in order to further his self-interested agenda.